Optimal Treatment Duration of Pseudomonas aeruginosa Infections in Allogeneic Hematopoietic Cell Transplant Recipients. (23rd June 2020) - Olearo, Flaminia; Kronig, Ilona; Masouridi-Levrat, Stavroula; Chalandon, Yves; Khanna, Nina; Passweg, Jakob; Medinger, Michael; Mueller, Nicolas J; Schanz, Urs; Van Delden, Christian; Neofytos, Dionysios
Abstract: In a large, multicenter, contemporary, 8-year, cohort study, one third of allogeneic-hematopoietic cell transplant (HCT) recipients with Pseudomonas aeruginosa (PSA) infection developed a recurrent infection within 3 months. Antibiotic treatment duration of ≥14 days was the only significantly associated variable with reduced recurrence rates of PSA infections in allogeneic-HCT recipients. Abstract : In a large retrospective multicenter 8-year cohort study, Pseudomonas aeruginosa (PSA)-infections in allogeneic hematopoietic cell transplant recipients were associated with 30% recurrence rate. A minimum of 14-day antibiotic treatment was required in order to prevent recurrent PSA-infections.?